HASIL BELAJAR BAHASA JERMAN SISWA SMA DENGAN MENGGUNAKAN LKS ‘’SIE LERNEN DEUTSCH’’ - FATMAWATI, DENIK (LATERNE, 2016)
This study in the background backs lack of interest of students towards learning the German language. In order to achieve the learning objectives, it is necessary teaching materials that can make students more independent learning so that learning is not centered on guru.Salah one additional teaching materials LKS Sie Deutsch lernen which has been developed by Fitri Kasanti. This research was conducted to find out the results of class X student MIA 1 SMAN 2 SIDOARJO using LKS Sie lernen Deutsch. This research uses qualitative research. The problem of this study is ' How does learning outcomes German language high school students of class X using the second semester of LKS Fitri Kasanti in the title ' Sie Deutsch lernen '. The purpose of this study is ' Describing the results of learning German high school students of class X the semester by using LKS Fitri Kasanti under the heading ' Sie lernen Deutsch '. The data from this study were drawn from the test results before using worksheets and after using LKS Sie lernen Deutsch , The results were analyzed to determine student learning outcomes after using LKS Sie lernen Deutsch. The results of the feasibility LKS seen from the student questionnaire that has been deployed and the questionnaire showed a value of 86.9%. The results of the questionnaire according to the value of the qualifying table Arthana (2005) shows the results with the criteria very baik.Hasil research shows that LKS Sie Deutsch lernen can be used as teaching materials German language learning in the four skills of reading, writing, listening and speaking. It is seen from the results of class X student of SMAN 2 SIDOARJO MIA 1 of the first meeting until the fourth has risen an average of the first meeting of 69 still under KKM. 86 And the second meeting, the third meeting of the fourth meeting of 86 and 91 showed that the average value of students has increased and meets the KKM.Keywords: learning outcomes and LKS Sie Deutsch lernen  Keywords: learning outcomes and LKS Sie lernen Deutsch .